Human immunoglobulin G responses to Cimex lectularius L. saliva. (22nd June 2020) - Sheele, Johnathan M.; Ferrari, Brian; Goddard, Jerome; Schlatzer, Danie; Lundberg, Kathleen C.; Guinto, Katirina; Embers, Monica E.; Young, Andrew B.; Ridge, Gale E.; Damiani, Giovanni; McCormick, Thomas S.
Abstract: Aims: To investigate the immunoglobulin (Ig) G response after being fed upon by Cimex lectularius L. Methods and Results: Participants were fed upon by three male C lectularius insects weekly for a month. Blood was obtained before the feeding and at the last feeding, which was used for immunoblots against bed bug salivary gland extract, with antihuman Immunoglobulin G (IgG) secondary antibodies. No consistent IgG changes developed in 11 humans serially fed upon by C lectularius . Two participants had new IgG responses to proteins at molecular weights of approximately 12‐13 kDa, and one had an IgG response to a protein at approximately 40 kDa. At the last study visit, more intense IgG bands to proteins at molecular weights of 12‐13 kDa had developed in 55% of participants (6/11) and at molecular weights of ≈30, ≈40 and ≈70 kDa in 45% (5/11) compared with the first study visit. Nitrophorin and apyrase were the most common C lectularius proteins identified with liquid chromatography‐tandem mass spectrometry in both crushed bed bug salivary gland extract and post–bed bug feeding extract. Conclusions: Human participants did not have consistent IgG responses to crushed C lectularius salivary gland extract.